Identifikasi Jamur Dermatofita pada Infeksi Tinea Unguium Kuku Kaki Petugas Kebersihan di Daerah Sekitar Jalan Abd.Kadir Kota Makassar - Ditaellyana Artha; Lilis Oktasaputri (Prodi D-III Analis Kesehatan niversitas Indonesia Timur, 2020)
Dermatophyte fungi are a group of fungi that have the ability to form molecules that bind to keratin and use it as a source of nutrition to form clones. Tinea unguium is a fungal infection of the nails caused by dermatophytes, nondermatophytes, and yeasts. Nails are covers and protectors of the tips of the fingers and toes which are used to help fingers hold objects. A janitor is someone who is in charge of maintaining a clean environment whose scope of work is also around dirty, hot, and humid areas. This study aims to identify dermatophyte fungi in infection with Tinea unguium toenails of janitors in the area around Jalan Abdul. Head of Makassar City. The benefit of research is to add insight to the public about nail health. The sample used was from 3 janitors. And the sampling technique is total sampling. The results of the research that has been carried out are that from all samples no dermatophyte fungi were found, but there were other types of fungi, namely Candida sp, Penicillium sp, Aspergillus niger, Aspergillus fumigatus.